Elevations in vascular markers and eosinophils in chronic spontaneous urticarial weals with low‐level persistence in uninvolved skin. (24th August 2014) - Kay, A.B.; Ying, S.; Ardelean, E.; Mlynek, A.; Kita, H.; Clark, P.; Maurer, M.
Summary Background In chronic spontaneous urticaria (CSU) mast cell activation together with inflammatory changes in the skin are well documented and may play an important role in mechanisms of tissue oedema. Objectives To confirm and extend these observations by measuring microvascular markers, leucocytes and mast cell numbers in lesional and uninvolved skin and to compare findings with a control group. Methods Paired biopsies (one from 4–8‐h spontaneous weals and one from uninvolved skin) were taken from eight patients with CSU and nine control subjects and studied using immunohistochemistry and confocal microscopy using the lectin Ulex europaeus agglutinin 1 (UEA‐1). Results Lesional skin in CSU contained significantly more CD31+ endothelial cells; CD31+ blood vessels, neutrophils, eosinophils, basophils and macrophages; and CD3+ T cells than nonlesional skin. Increased vascularity was confirmed by confocal imaging using the lectin UEA‐1. Uninvolved skin from CSU contained significantly more CD31+ endothelial cells, CD31+ blood vessels and eosinophils compared with the control subjects. There was a threefold increase in mast cell numbers when CSU was compared with controls but no difference was observed between lesional and uninvolved skin. Conclusions Increased vascular markers together with eosinophil and neutrophil infiltration are features of lesional skin in CSU and might contribute to tissue oedema. Eosinophils and microvascular changes persist in uninvolved skin, which, together with increased mast cells, suggests that nonlesional skin is primed for further wealing.